2017
DOI: 10.1007/s11265-017-1260-8
|View full text |Cite
|
Sign up to set email alerts
|

Design Flow for GPU and Multicore Execution of Dynamic Dataflow Programs

Abstract: Dataflow programming has received increasing attention in the age of multicore and heterogeneous computing. Modular and concurrent dataflow program descriptions enable highly automated approaches for design space exploration, optimization and deployment of applications. A great advance in dataflow programming has been the recent introduction of the RVC-CAL language. Having been standardized by the ISO, the RVC-CAL dataflow language provides a solid basis for the development of tools, design methodologies and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Increasing attention has been paid over the past few years to dataflow programming in the field of programming multicore and heterogeneous computing platforms [17][18][19][20][21][22]. As outlined by the various studies that can be found in the literature, one of the most prominent use cases is the execution of dataflow programs on GPU platforms.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing attention has been paid over the past few years to dataflow programming in the field of programming multicore and heterogeneous computing platforms [17][18][19][20][21][22]. As outlined by the various studies that can be found in the literature, one of the most prominent use cases is the execution of dataflow programs on GPU platforms.…”
Section: Related Workmentioning
confidence: 99%
“…As outlined by the various studies that can be found in the literature, one of the most prominent use cases is the execution of dataflow programs on GPU platforms. In this direction, refer for example to [17][18][19][20][21][22]. Specific to dynamic programs and implemented on GPU platforms using RVC-CAL, the works presented in [23] and in [24] show two different approaches on how to use OpenCL APIs to implement, partition, and subsequently execute RVC-CAL SW programs.…”
Section: Related Workmentioning
confidence: 99%
“…It is a data-centric model and can be represented as a graph, where nodes are the operations that are applied to the incoming data, and edges represent the flow of data. It is used in different domains like signal processing [2], [3], [4], [5] and image [6] or video processing [7]. New languages based on this approach have also been developed [8], [9], [10] and [11].…”
Section: Introductionmentioning
confidence: 99%